2020
DOI: 10.1590/2317-1545v42237826
|View full text |Cite
|
Sign up to set email alerts
|

Viability of seedling image analysis (Vigor-S) to determine the physiological potential of melon seeds

Abstract: Melon is a vegetable crop of food and nutritional importance whose cultivation is growing worldwide. In this sense, investments in technologies are necessary, especially regarding the quality of seeds used in the establishment of new areas. This study aimed to verify the effectiveness of the Automated Seed Vigor Analysis System (Vigor-S) in the evaluation of the physiological potential of melon seeds. Eight seed lots (four lots of the hybrid Supreme and four of the hybrid Premier) were used. The physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…As well as, Rego et al (2021) in cowpea seeds, where the automated analysis provided a positive correlation with the traditional vigor tests. Leite et al (2020) found that automated analysis with Vigor-S ® was effective in determining the physiological potential of melon seeds.…”
Section: Discussionmentioning
confidence: 99%
“…As well as, Rego et al (2021) in cowpea seeds, where the automated analysis provided a positive correlation with the traditional vigor tests. Leite et al (2020) found that automated analysis with Vigor-S ® was effective in determining the physiological potential of melon seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The Vigor-S system combines parameters that are strongly correlated with soybean seed vigor evaluated by traditional tests (Rodrigues et al, 2020). Research results from other species, such as common bean (Medeiros et al, 2019), maize (Castan et al, 2018), and melon (Leite et al, 2020), have also highlighted this potential of the system. The aim of this study was to determine if computerized image analysis of seedlings enables the phytotoxicity of chemical treatment of soybean seeds to be assessed in an effective and simplified manner.…”
Section: Introductionmentioning
confidence: 92%